Management Model based on Total Productive Maintenance (TPM) and Six Sigma to increase Overall Equipment Effectiveness (OEE) in a Textile and Apparel Company in Lima, Peru - Ortiz Porras, Jorge Enrique (2025)
This article addresses the challenge of low overall equipment effectiveness (OEE) within the textile industry. It identifies the need to enhance equipment availability, quality, and performance to tackle sectoral challenges. The main objective of this research study aimed to develop and implement a management model based on total productive maintenance (TPM) and Six Sigma, using a textile company as a case study. A sample of 28 machines from the Weaving Department was taken and various tools were applied, including internal analysis, process flow diagram (PFD), failure mode and effects analysis (FMEA), Pareto analysis, cause-and-effect matrix, 5S, TPM, I-MR charts, and control plans. As a result, a remarkable increase of 9.09% in OEE was achieved, demonstrating specific improvements of 5.18% in equipment availability, 4.23% in performance, and 1.6% in quality.